Psychosocial factors driving common substances used among Ghanaian senior high school students - Rachael Asantewaa Darko; Franklin N. Glozah (BMC Research Notes)
Abstract Objective Substance use among adolescents poses a significant public health challenge, particularly in low- and middle-income countries like Ghana. This study investigates the prevalence of substance use and its psychosocial correlates among in-school adolescents in Ghana, with the goal of identifying key risk and protective factors to inform culturally appropriate prevention and intervention strategies. Results The findings revealed distinct patterns of substance use linked to social and familial influences. Male students, those living with relatives, and those with peers who drank alcohol had a higher likelihood of alcohol use. Students who engaged in part-time work or had family members who smoked were more likely to use cigarettes. Older adolescents and those with friends who used shisha showed increased shisha consumption. Notably, limited social media exposure and living with parents or siblings were associated with reduced marijuana use. Furthermore, students who reported substance use exhibited signs of potential substance use disorder. The study underscores the strong influence of peer and family substance use behaviours on adolescent substance uptake. These findings highlight the need for targeted, context-specific interventions that address psychosocial risk factors while reinforcing protective family and social dynamics to promote adolescent well-being in Ghana and similar settings.